Menuju Keluarga Sakinah (Membentuk Keluarga Sakinah Berdasarkan Perspektif Islam - Muhadi Zainuddin (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2005)
Marriage, in Islamic teaching is one important aspect to lead a life in accordance with the religion. Beginning from marriage, a Muslim family can build their life foundation. An Islamic family has unique characteristics such as: it function as a place to cultivate love, mutual respect and a plce to perform religious practices, which in turn will bring to the family a sence of happines, peace, security and safety (sakinah mawaddah wa rahmah). “Sakinah” (meaning happines) is the terminal value of every Muslim family. As the targeted end of every married couple, Sakinah is determined by how the couple go through the process of making and running a family which include: choosing a spouse (such as important consideration to select the most prospective partner from religious perspective), straightening the intention (niat), understanding the unique psychological disposition of the partner, fulfilling the rights of family member (including children) and performing duties and obligation, choosing the best strategy for coping with family challenges and ability to family problems (family problem solving).Kata kunci: keluarga sakinah